Progressive apraxia of speech in Quebec French speakers: A case series. Issue 3 (11th February 2021) - Bouvier, Liziane; Monetta, Laura; Laforce, Robert Jr; Vitali, Paolo; Bocti, Christian; Martel‐Sauvageau, Vincent
Abstract: Background: The term progressive apraxia of speech (PAOS) is used to describe speakers presenting with isolated or dominant apraxia of speech in the context of a neurodegenerative syndrome, including primary progressive apraxia of speech (PPAOS) and dominant progressive apraxia of speech (DAOS), respectively. Its motor speech profile has been increasingly explored in the last decade, but description remains vague and very English oriented, although the effect of speakers' language on motor speech phenotypes is increasingly recognized. Although some studies suggest that speakers presenting with isolated PAOS (PPAOS) versus dominant PAOS with concomitant aphasia (DAOS) should be differentiated, distinct characteristics of the two presentations are unclear. Furthermore, a careful description of their clinical presentation in languages other than English is required. Aims: To describe the motor speech characteristics of Quebec French‐speaking participants with prominent PAOS and to explore the communication profile of those presenting more specifically with isolated PAOS (PPAOS), and with dominant PAOS and concomitant aphasia (DAOS). Methods & Procedures: A thorough effort to recruit all speakers presenting with PAOS in the larger population areas of the province of Quebec was conducted over a 3‐year span. A total of nine participants with PAOS (pwPAOS; PPAOS = 5, DAOS = 4) underwent a comprehensive language and motor speech assessment, and a cognitive screening. Their performance was compared with 30 matched healthy controls. Outcomes & Results: As a group, pwPAOS differed from healthy speakers on all acoustic and perceptual measures. The PPAOS and PAOS subgroups were similar on several measures, but participants from the PPAOS subgroup tended to perform better on articulatory measures and maximum speech rate tasks. Conclusions & Implications: This study provides an in‐depth analysis of motor speech characteristics of PAOS in Quebec French speakers and adds further evidence for the differentiation of PPAOS and DAOS. Combining simple perceptual and acoustic analyses represent a promising approach to distinguish the two variants and identify treatment targets. What this paper adds What is already known on this subject: Progressive apraxia of speech (PAOS) is a neurodegenerative syndrome characterized by progressive and initially isolated or dominant apraxia of speech (primary progressive apraxia of speech [PPAOS] and dominant progressive apraxia of speech [DAOS], respectively). Studies mostly report articulatory and prosodic deficits in PAOS, but concomitant deficits such as dysarthria and executive dysfunction are also reported. The description of motor speech skills in PAOS remains vague and English‐oriented. Studies suggest that speakers presenting with isolated PAOS vs dominant PAOS with concomitant aphasia should be differentiated, but distinct characteristics of the two presentations are unclear. What this study adds to existing knowledge: To the best of the authors' knowledge, this study is the first to report transversal data of Quebec‐French participants with PPAOS and DAOS. Moreover, this study is a first step towards identifying potential characteristics that could facilitate the diagnosis of PPAOS and DAOS in Quebec French. It makes a significant contribution to our understanding of progressive apraxia of speech in different cultural languages. What are the potential or actual clinical implications of this work?: This study also initiates the search for sensitive tasks for the diagnosis of those speakers (which is an important process), in addition to identifying the core characteristics of PAOS, DAOS, and PPAOS in the development of an assessment battery for this population.